An Overview of the Indonesian Abalone Industry: Production, Market, Challenges, and Opportunities - Dwi Eny Djoko Setyono; Hollanda Arief Kusuma (BIO Web of Conferences, 2023)
The Indonesian abalone industry has been experiencing growth in recent years and holds significant potential for further expansion. This paper provides a comprehensive review of the current state of the abalone industry in Indonesia, including production processes, markets, and trade, as well as the challenges and opportunities faced by the industry. The study found that the growth of the Indonesian abalone industry is driven by both the domestic market and the increasing demand for Indonesian abalone in international markets. Despite these opportunities, the industry faces various challenges, such as illegal fishing practices, intense competition, and fluctuating prices. The Indonesian government has implemented regulations to promote sustainable harvest and trade practices to address these challenges. The industry is focused on producing high-quality abalone to maintain its competitive position in the global market. The Indonesian abalone industry needs to overcome these challenges To sustain its growth in the future, expand its market reach through international trade, and continuously produce high-quality products. This review provides valuable insights into the Indonesian abalone industry and highlights potential future directions for growth. The findings of this study could be useful for industry players, policymakers, and researchers interested in the development of the Indonesian abalone industry.